1981
DOI: 10.1039/p19810001235
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of condensed tannins. Part 4. A direct biomimetic approach to [4,6]- and[4,8]-biflavanoids

Abstract: The generation of flavanyl-4-carbo-cations from flavan-3,4-diols and their condensation with nucleophilic flavan-3-01s to form [4,6]-and [4,8]-biflavanoids at ambient temperatures and under mildly acidic aqueous conditions apparently simulates the initial step in condensed tannin formation in a number of natural sources. The stereospecificity (or stereoselectivity) of the reaction is conditioned mainly by the 2,3-cis or 2,3-trans stereochemistry of the parent flavan-3,4-diol, but also by the nucleophilicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…Such asymmetric labeling supports the mechanism of a carbocationmonomer condensation for polymer formation rather than a condensation of similar units (5). Such asymmetry would also be expected, because the pool of carbocation would be very small relative to that of the flavan-3-ol monomers (2 (Fig. 4).…”
Section: Asymmetricmentioning
confidence: 79%
See 1 more Smart Citation
“…Such asymmetric labeling supports the mechanism of a carbocationmonomer condensation for polymer formation rather than a condensation of similar units (5). Such asymmetry would also be expected, because the pool of carbocation would be very small relative to that of the flavan-3-ol monomers (2 (Fig. 4).…”
Section: Asymmetricmentioning
confidence: 79%
“…1). Several groups have demonstrated that dimers similar to natural products can be formed nonenzymically upon the addition of a diol formed as a reduction product of dihydroquercetin, or the appropriate carbocation (2)(3)(4). Studies with "C-labeled phenylalanine and cinnamic acid fed to intact shoots have provided direct evidence for this mechanism by demonstrating the greater incorporation of label into the 'upper' (derived from the carbocation) than into the 'lower' (derived from the flavan-3-ol) unit (5).…”
mentioning
confidence: 99%
“…Five mg (+)-dihydroquercetin was stirred into 1 ml ofethanol and 3 mg NaBH4 was added over a 30-min period (1). After 1 h, 2 ml of 0.1 N HCI and 10 ml of H20 were added.…”
mentioning
confidence: 99%
“…Nonenzymic Preparation of Flavan-3-ols (1,5). Five mg (+)-dihydroquercetin was stirred into 1 ml ofethanol and 3 mg NaBH4 was added over a 30-min period (1).…”
mentioning
confidence: 99%
“…9 closely related to that of fisetinidol-(4a→6)-catechin, which has already been reported. 10) It showed negative Cotton effect at 200-220 nm in the CD spectrum defined as an a orientation at C-4, that is, the 4S configuration. However, the CD spectrum of compound 2 showed a strong positive Cotton effect at 216 nm, which defined a 4b orientation.…”
Section: Resultsmentioning
confidence: 99%